Ion Induced Changes in the Structure of Bordered Pit Membranes - Lee, Jinkee; Holbrook, Noel Michele; Zwieniecki, Maciej A. (Frontiers in Plant Science, 2012)
Ion-mediated changes in xylem hydraulic resistance are hypothesized to result from hydrogel like properties of pectins located in the bordered pit membranes separating adjacent xylem vessels. Although the kinetics of the ion-mediated changes in hydraulic resistance are consistent with the swelling/deswelling behavior of pectins, there is no direct evidence of this activity. In this report we use atomic force microscopy (AFM) to investigate structural changes in bordered pit membranes associated with changes in the ionic concentration of the surrounding solution. When submerged in de-ionized water, AFM revealed bordered pit membranes as relatively smooth, soft, and lacking any sharp edges surface, in contrast to pictures from scanning electron microscope (SEM) or AFM performed on air-dry material. Exposure of the bordered pit membranes to 50 mM KCl solution resulted in significant changes in both surface physical properties and elevation features. Specifically, bordered pit membranes became harder and the fiber edges were clearly visible. In addition, the membrane contracted and appeared much rougher due to exposed microfibers. In neither solution was there any evidence of discrete pores through the membrane whose dimensions were altered in response to the ionic composition of the surrounding solution. Instead the variable hydraulic resistance appears to involve changes in the both the permeability and the thickness of the pit membrane.